Wireless sensor networks, internet of things, and their challenges - Azrul Amri, Jamal; Nor Aida, Mahiddin (2019)
Internet of Things (IoT) is currently one of the top technological concepts where users and objects are interconnected using wired and wireless technologies such as Wireless Sensor Networks (WSNs), ZigBee, NFC, RFID, GPRS, LTE and Bluetooth, anywhere and anyplace. Within the past ten years, the idea of IoT has drawn massive consideration from both the business and research communities. Application domains may have many substantial benefits by means of an IoT approach. The idea of this field of study is to portray a basic knowledge of smart environmental monitoring system based on IoT. It has been stated in various studies in the past that IoT is facing multiple issues such as authentication, identification, availability, security and privacy, and socio-technical trust system (STTS). Nowadays, existing smart environments are continuing to face major IoT setbacks and challenges with regards to security, privacy, and STTS. Creating a STTS comparison in IoT is one of the principal significant breakthroughs necessary for building stable structures which will serve to eliminate doubt and technical setbacks. This study will present an outline of security, privacy and STTS in IoT while using a simulation method for comparing the results and justifying the outcomes. It aims to highlight and define the effectiveness of trust-management and how it should be exploited in IoT. The results will be indicated based upon past and present study result comparisons.